Comparison of the Hydraulic Effect of Straight and Curved Groynes in the Curved Canal (Journal of Engineering, 2025)
The dynamics of flow and turbulence surrounding groynes in a bending canal are highly complex behaviors. This study, which was conducted by HEC-RAS version 6.5 software, focuses on the use of curved groynes in 180°-degree bend canals to study the flow behavior in bending by calculating the velocity of flow along the concave outer edge, in which bank erosion usually occurs, the flow velocity at the inner edge, and calculating the vortices that form between the groynes. The results showed that the curved groynes outperformed the commonly used straight groynes in the same conditions. The findings indicate that curved groins decrease the flow velocity at the outer edge by 99%, while straight groins achieve a reduction in flow velocity ranging from 68% to 98%. Due to the decrease in the canal section, the increase in flow velocity at the inner edge was 28% for curved groynes and 34% for straight groynes. Additionally, curved groynes reduce the vortex value within the groynes field, thereby reducing the scouring rate in the canal bed.